Exploration of Zimbabwean migrant women's beliefs and practices surrounding access, utilisation of contraceptives and antenatal services in South Africa - Dunjana, Sibonginkosi (My University, 2021)
Maternal health of vulnerable populations including migrants remains poor, especially when compared with non-migrants in South Africa. However, over the past decades access to contraceptive issues and antenatal services have been placed at the periphery of reproductive health discourses. Using qualitative Socio-ecological and Intersectionality approaches, this study sought to contribute in closing this gap by investigating beliefs and practices surrounding contraceptives and antenatal care among Zimbabwean migrant women. In-depth interviews were conducted with 14 women in Johannesburg and Pretoria (South Africa), identified through purposive sampling and snowballing. Thematic analysis was used to analyse data. Evidence from the study reveals that there is prevalent use of the Zimbabwean oral pills among other multiple contraceptives used by nationals of this country who have migrated to South Africa. Participants reported that they preferred Zimbabwean contraceptives especially the oral pill over the South African ones, owing to the side effects experienced from local options. With regards to antenatal care, the study established that Zimbabwean migrant women use traditional medicine such as elephant dung and herbs in concurrence with biomedicine. This practice is founded on the fear of maternal and infant deaths which remains high in developing countries. They believe that the use of traditional medicine prevents labour complications that can lead to cesarean births, prolonged labour, maternal, foetal and neonatal mortality. More importantly, the study established that Zimbabwean migrant women’s beliefs and practices relating to contraception or antenatal care are a continuation from their country of origin. These continuities are instituted and facilitated through a series of transnational activities, maintaining social ties, and communication. Findings show that although migration transforms some of the migrants’ beliefs and practices, most of these socio-cultural aspects are deep rooted, enduring even after resettlement, regardless of available contraceptive options and antenatal care services in South Africa. The study further noted that, although there are commonalities among the women’s beliefs and practices, their experiences of contraception and antenatal care are heterogeneous owing to the influences of multiple intersecting factors from the different levels of the socio-ecological framework such as class, documentation status and personal past experiences among other factors. The study concludes that Zimbabwean women’s beliefs and practices surrounding contraceptives or antenatal care, are complex, multilayered, characterised by multiple intersections between personal, social, structural factors from both the country of origin and destination. Migrant transnationalism is, therefore, a resource which facilitates continuities with country of origin beliefs and practices surrounding contraception and antenatal care. These findings reflect a need for future research on experiences of other nationals with local contraceptives, and how they cope with the desire to use their country of origin contraceptive options or traditional medicine for antenatal care, considering the proximity of some of their countries with South Africa.
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Migration and Displacement to the Faculty of Humanities, University of the Witwatersrand, 2021